show the effect of the physical education lesson while using the interactive ground games with the 4th grade students to enhance their kinetic abilities - Shahad Jumaa Dr. Zina Abdul-salam (الرياضة المعاصرة)
The study is meant to show the effect of the physical education lesson while using the interactive ground games with the 4th grade students to enhance their kinetic abilities.